2018
DOI: 10.1186/s40851-018-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Draft genome of Dugesia japonica provides insights into conserved regulatory elements of the brain restriction gene nou-darake in planarians

Abstract: BackgroundPlanarians are non-parasitic Platyhelminthes (flatworms) famous for their regeneration ability and for having a well-organized brain. Dugesia japonica is a typical planarian species that is widely distributed in the East Asia. Extensive cellular and molecular experimental methods have been developed to identify the functions of thousands of genes in this species, making this planarian a good experimental model for regeneration biology and neurobiology. However, no genome-level information is availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 61 publications
2
37
0
1
Order By: Relevance
“…After removal of low quality, truncated and adapter chimera sequences, read depth was 173, 192 and 196 M read pairs. To analyse this experiment we generated novel annotations (see Methods) of the most recent S. mediterranea genome assembly [47] and the recently sequenced D. japonica genome [48]. We mapped 96% and 85% of S. mediterranea and D. japonica reads to gene models in their respective gene annotations.…”
Section: Single-cell Transcriptomic Analysis Of Acme-dissociated Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…After removal of low quality, truncated and adapter chimera sequences, read depth was 173, 192 and 196 M read pairs. To analyse this experiment we generated novel annotations (see Methods) of the most recent S. mediterranea genome assembly [47] and the recently sequenced D. japonica genome [48]. We mapped 96% and 85% of S. mediterranea and D. japonica reads to gene models in their respective gene annotations.…”
Section: Single-cell Transcriptomic Analysis Of Acme-dissociated Cellmentioning
confidence: 99%
“…The S. mediterranea S2F2 genome [47] was downloaded from Planmine, and the D. japonica v 1.0 genome [48] was downloaded from http://www.planarian.jp. De novo gene models were created for both S. mediterranea and D. japonica.…”
Section: Read Mapping Barcode Extraction and Matrix Productionmentioning
confidence: 99%
“…Classical inquiry into planarian regeneration involved diverse injuries and transplantations. A suite of molecular and cellular tools have enabled a recent era of intensive molecular genetic inquiry into planarian regeneration (Umesono et al, 1997;Sá nchez Alvarado and Newmark, 1999;Newmark and Sá nchez Alvarado, 2000;Reddien et al, 2005a;Hayashi et al, 2006;Wagner et al, 2011;Wurtzel et al, 2015;An et al, 2018;Fincher et al, 2018;Grohme et al, 2018;Plass et al, 2018;Zeng et al, 2018). Much excellent and fascinating work on planarian biology will not be reviewed here, such as the role of myriad molecules that give planarian stem cells (neoblasts) their attributes, the molecular genetics of the planarian germline, organ formation and function, signaling pathway function and evolution, cilia, genome repair and protection, aging, epigenetics, regulatory RNAs, immune biology, and planarian embryogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that many of the problems associated with the amplification and sequencing of planarian molecular markers may be solved by applying next generation sequencing (NGS) methodologies (Sluys and Riutort 2018). This new era has started already, and in recent years genomes and transcriptomes of freshwater planarians have already been sequenced (Egger et al 2015;An et al 2018;Grohme et al 2018;, contributing new anonymous nuclear markers that can be used as phylogenetic tools. There are even bioinformatic pipelines that can help in the discovery of these markers using NGS data as input (Frías-López et al 2016).…”
Section: Datasets and Phylogenetic Analysismentioning
confidence: 99%